Aquifer Characterization Through GPR and Borehole Analysis : Eau Claire Municipal Well Field, Wisconsin - Green, Mark M.; Keicher, Patrick A. (My University, 2014)
Our project's goal is to improve characterization of the aquifer supplying the Eau Claire municipal well held by correlating borehole data with GPR profiles to produce stratigraphic models at a higher degree of accuracy than traditional methods. Using a pulseEKKO 100 system, GPR data was collected across a 150 m and two 50 m transects to a depth of 12 m using a frequency of 100 MHz with a 0.5 m step size and 1 m antennae separation. The results show two facies representing a migrating sidebar and an expanding floodplain. Borehole data was collected to a depth of 30 m revealing grain size ranging between medium sand to gravel. Combining these data will ultimately lead to more accurate models than those produced using only point-source data. This method is effective in many geologic settings and can provide hydrogeologists with an accurate, cost-effective way to characterize aquifers without relying on costly point-source data.
Color poster with text, images, and graphs.
Keywords: Strandplain; PulseEKKO100 system; Ground penetrating radar; Posters